Business and cultural influences on sustainability in 3D design modeling - Ghazali, Ihwan; Tanjung, Tia (Human Resource Management Academic Research Society, 2024)
There is an increasing focus on sustainability in the global three-dimensional (3D) design modeling industry. Businesses are encouraged to prioritize profitability and integrate sustainable practices into their 3D models. However, customer preferences for sustainable designs may vary due to cultural influences, which can impact the effectiveness of marketing strategies. This study aims to explore the influence of cultural values on the adoption and perception of sustainability in 3D design modeling. A pretest was conducted to ensure the reliability and validity of the questionnaire. The collected data were analyzed using satisfaction levels, confirmatory factor analysis, and structural equation modeling to assess the impact of cultural dimensions on sustainable 3D design preferences. The results revealed that specific cultural dimensions, such as uncertainty avoidance and long-term orientation, significantly shape customer preferences for sustainable 3D designs. Additionally, eco-friendly design features and product longevity emerged as critical factors influencing customer satisfaction in different cultural contexts. The insights gained from this study provide valuable guidance for businesses and policymakers in aligning 3D design practices with consumer preferences for sustainability. These findings can help organizations develop products that meet sustainability goals while appealing to culturally diverse markets. This research offers essential information for designers and businesses to create 3D design models that incorporate sustainable elements to consumer preferences across various cultural contexts.